(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The creationist origin of human nature and the right to euthanasia. An analysis from the perspective of Christian ethics. Contemporary Western society is polarized around two diametrically opposed perspectives: the traditional Christian view and the secular liberal view. While the Christian worldview affirms God’s sovereignty over human life and death, the secular humanist worldview upholds the individual’s right to freedom and personal self-determination. The present article analyzes the ethics of euthanasia and assisted suicide, especially the issue of the human right to decide the moment of death, from the perspective of the creationist origin of human nature and Christian ethics, respectively. After defining and classifying euthanasia, taking into account issues such as the patient, the way in which death occurs and the means of sustaining life, we will emphasize that the creationist origin of human nature is the foundation on which Christian ethics is based on euthanasia. In the second part of the study we will review the main pro- euthanasia arguments, focusing on the argument for the human right to autonomy and self-control, as a basis for the human right to die. The conclusion we will reach is that in reality there is no right to die. Rather, the legalization of euthanasia is a cosmetic expression of the secularized man’s inability to cope with the moment of death and to stand by his fellows in front of the great threshold.